Learning Outcomes: How does the Experimentation of the MEA and STAD Models? - Ulfah Hidayati; Devi Sela Eka Selvia; Nurul Azizah; Baharudin; Beti Susilawati (Inspiratif Pendidikan, 2024)
This study aims to determine the effectiveness of the MEA and STAD learning models on student learning outcomes in Religious Education (PAI) at SMA Negeri 10 Bandar Lampung. The research uses a quantitative approach with a quasi-experimental design. The sampling technique employed is probability sampling, specifically simple random sampling, where classes are randomly selected without considering their grade levels. The instrument used in this study is a multiple-choice test. Class X.1 serves as the control group, while classes X.5 and X.7 are the experimental groups. The results of this study show that the normality test yielded a value of 0.00 < 0.05, indicating that the data is not normally distributed. Therefore, a non-parametric test was conducted using the Mann-Whitney test, with results of 1.00 for the MEA model and 0.007 for the STAD model. The homogeneity test yielded a result of 0.407 > 0.05, indicating that the data is homogeneous. The hypothesis test using one-way ANOVA yielded a result of 0.376 > 0.05, so it can be concluded that H0 is accepted and Ha is rejected, meaning there is no significant effect of the MEA and STAD learning models on student learning outcomes. This study offers a new contribution by comparing two learning models that have been more commonly applied to mathematics subjects rather than PAI. Additionally, this research responds to issues in education such as low learning motivation and the lack of innovative teaching models, with the hope of contributing to the field of education, particularly in Religious Education (PAI).